Treatment preferences for medication or surgery in patients with deep endometriosis and bowel involvement – a discrete choice experiment. (27th December 2021) - Metzemaekers, Jeroen; van den Akker‐van Marle, M. Elske; Sampat, Jonathan; Smeets, Mathilde J. G. H.; English, James; Thijs, Elke; Maas, Jacques W. M.; Willem Jansen, Frank; Essers, Brigitte
Abstract: Objective: To study the preferences of women with deep endometriosis (DE) with bowel involvement when they have to choose between conservative (medication) or surgical treatment. Design: Labelled discrete choice experiment (DCE). Setting: Dutch academic and non‐academic hospitals and online recruitment. Population or Sample: A total of 169 women diagnosed with DE of the bowel. Methods: Baseline characteristics and the fear of surgery were collected. Women were asked to rank attributes and choose between hypothetical conservative or surgical treatment in different choice sets (scenarios). Each choice set offered different levels of all treatment attributes. Data were analysed by using multinomial logistic regression. Main Outcome Measures: The following attributes – effect on/risk of pain, fatigue, pregnancy, endometriosis lesions, mood swings, osteoporosis, temporary stoma and permanent intestinal symptoms – were used in this DCE. Results: In the ranking, osteoporosis was ranked with low importance, whereas in the DCE, a lower chance of osteoporosis was one of the most important drivers when choosing a conservative treatment. Women with previous surgery showed less fear of surgery compared with women without surgery. Low anterior resection syndrome was almost equally important for patients as the chance of pain reduction. Pain reduction had higher importance than improving fertility chances, even in women with desire for a future child. Conclusions: The risk of developing low anterior resection syndrome as a result of treatment is almost equally important as the reduction of pain symptoms. Women with previous surgery experience less fear of surgery compared with women without a surgical history. Tweetable Abstract: First discrete choice experiment in patients with deep endometriosis. Tweetable abstract: First discrete choice experiment in patients with deep endometriosis.